O farmacêutico em tempo integral e as práticas em saúde na estratégia de saúde em família - Nascimento, Juçara Barga Do [UNIFESP] (2021)
Introduction: This research presents the activity of the pharmaceutical professional in the Brazilian Unique Health System (SUS) which, even inserted in this public policy, it has a timid performance in Primary Care. From the perspective of comprehensiveness, concern is expressed every day the guarantee of access to health, supported by the assertion that this guiding axis leads to health practices unimaginable until then. It is believed, therefore, that the Pharmacist supports this aspect, including the identification of this performance combined with interprofessional initiatives with the team of the Family Health Strategy. The study purpose is to evaluate the interprofessional collaboration of the health team of the Family Health Strategy (FHS), as well as the care exercises of the Pharmacist, when their full-time work activities are thus preserved. Method: exploratory-descriptive study with a qualitative approach, using the Interprofessional Team Collaboration Assessment Scale (AITCS II-BR), based on a cross-cultural translation by Bispo and Rossit (2019), which assesses the work of the health team for the Collaborative Interprofessional Practice. It consisted of applying this instrument containing 23 assertions, through the Likert Scale, divided into 3 dimensions: partnership, cooperation and coordination for Collaborative Practice. The attitudinal analysis used in the AITCS II-BR instrument was the mathematical treatment of means, whose assertions and dimensions were classified as "comfort zone" (3.68-5.0), "alert zone" (2.34-3, 67) and "danger zone" (1.0-2.33), categorizations that register in the comfort zone, a positive aspect of the research, in the alert zone, need for changes and in the danger zone, urgent intervention. The focus group was used only for the ESF Pharmacists and the treatment of group conversations was submitted to content analysis, determining lines that considered the contribution of the Pharmacist to the team and their interventions in the field of health care. Results: The research showed that the ESF team has collaborative engagement, the partnership and cooperation dimensions showed averages of 4.06 and 3.88 respectively, pointing these dimensions to the comfort zone, which demonstrates a positive aspect of teamwork in the development of interprofessionalism. The coordination dimension revealed a result in the alert zone, the average obtained was 3.36, whose result demonstrates the weakness of this dimension, indicating the need for the team to develop better for interprofessionalism. The focus group identified a good participation of the Pharmacist with the team, with statements that promote interprofessional actions and in line with the integrality axis of the SUS. Their full-time presence has contributed to the possibility of integrating themselves into the minimum team of the Family Health Strategy, thus breaking the silencing of health care, generated by the absence of this professional, this deficiency commonly observed when verifying the actions of the Pharmacist in Primary Health Care. Final considerations: The analysis of the AITCS II-BR showed that the professional inserted in the SUS policy has an interprofessional profile. It can be linked to the environment that develops the professional naturally for this aspect, because apparently they are initiatives linked to the intuitive and empirical field that lead them to such results. It is necessary to solidify this theme, from an intentional project for interprofessional education, identifying the weaknesses established by the usual uniprofessional training of health professionals. With the municipalization of all Primary Health Care, it will be possible to avoid the recurrent displacements of outsourced workers today, generating an improvement in the interprofessional articulation and professional training for the SUS. The creation of the Multiprofessional Residency can also contribute to the training process of these professionals. Continuing education is a fundamental resource for this achievement, capable of deepening and amplifying learning related to the Singular Therapeutic Project, shared leadership, improvement for an affectionate look at what the Extended Clinic establishes and many other concepts about interprofessionalism and health care. The view of most municipal managers on the involvement of the Pharmacist is still a challenge to be overcome, precisely because of their low participation in this type of service. Although SUS inducing policies increasingly place the need for this professional in technical-assistance activities, there are many planning, cultural, legal, organizational and human resources barriers that prevent the commitment of this social actor in the Health Strategy policy of the Family. Thus, every day in which he is inserted, the Pharmacist has demonstrated a better approach to the rational use of medicines, based on cooperation events.